Colonic budesonide delivery by multistimuli alginate/Eudragit® FS 30D/inulin-based microspheres as a paediatric formulation. (15th February 2023) - D'Amico, Vita; Arduino, Ilaria; Vacca, Mirco; Iacobazzi, Rosa Maria; Altamura, Davide; Lopalco, Antonio; Rizzi, Rosanna; Cutrignelli, Annalisa; Laquintana, Valentino; Massimo, Franco; De Angelis, Maria; Denora, Nunzio; et al.
Abstract: The purpose of this study was to develop an oral paediatric formulation of budesonide (BUD) for the treatment of inflammatory bowel disease. A formulation realized as microspheres using the prilling/vibration technique is proposed as an innovative drug delivery system ensuring BUD-specific colonic release in response to different triggers, such as pH, transit time, and resident microbiota. BUD, or the inclusion complex BUD/hydroxypropyl-β-cyclodextrin, was loaded into microspheres consisting of different ratios of alginate, Eudragit® FS 30D, with or without inulin. Sixteen formulations are produced that show high yields and encapsulation efficiencies, ensuring a homogenous distribution of BUD into the matrix. Microsphere diameters of <655 μm and promising flow properties make these systems suitable for oral administration to children. Swelling and drug release studies in simulated gastrointestinal fluid are used to demonstrate the response of microspheres to time and pH triggers. Studies in faecal medium highlight that drug release from microspheres with inulin is also influenced by microbiota.